1999
DOI: 10.2134/jeq1999.00472425002800010030x
|View full text |Cite
|
Sign up to set email alerts
|

In‐Stream Wetland Mitigation of Nitrogen Contamination in a USA Coastal Plain Stream

Abstract: Nonpoint source N from riverine origin is a major water quality problem throughout the world. Nitrogen removal from a contaminated (6.6 mg L−1, NO3‐N) stream was evaluated in this study using an instream wetland (ISW). The ISW was established at the exit of a 425‐ha USDA Water Quality Demonstration watershed in the Coastal Plain of North Carolina. It ranged in depth from about 0.2 to 2 m, and it was <1% (3.3 ha) the size of the watershed. The ISW dramatically lowered mean stream NO3‐N from 6.6 to 2.0 mg L−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…They are also a good choice for the ER of the SNWTP because this project is not only a major water transfer project from south to north in China, but also an ecological project with high landscape requirements. To date, FWS wetlands have been mainly used for treating domestic sewage [6,7] and livestock wastewater [8,9], controlling non-point pollution [10,11], rehabilitating and re-establishing rivers and wetlands [12], and improving river quality [13].…”
Section: Introductionmentioning
confidence: 99%
“…They are also a good choice for the ER of the SNWTP because this project is not only a major water transfer project from south to north in China, but also an ecological project with high landscape requirements. To date, FWS wetlands have been mainly used for treating domestic sewage [6,7] and livestock wastewater [8,9], controlling non-point pollution [10,11], rehabilitating and re-establishing rivers and wetlands [12], and improving river quality [13].…”
Section: Introductionmentioning
confidence: 99%
“…[21,[24][25][26]36,39] Relative to carbon and nitrogen concentration, all 3 of the methanol:nitrate concentrations (2:1, 10:1, and 20:1) seemed to function adequately. However, pushing the ratio lower could result in either lower denitrification or potentially incomplete denitrification.…”
Section: Laboratory Bioreactor Reaction Kineticsmentioning
confidence: 98%
“…Thus, a bioreactor of 1 m 3 would be required to treat 1 m 3 of drainage water in 1 h. This HRT would likely be very useful for much of the base and storm flow. For instance, Jaynes and Colvin [41] [21,24,26] As such, the IDS bioreactors offer the potential for requiring small bioreactor footprints, treating nitrate concentration hot spots, and treating moderate storm flows. Furthermore, the reaction rate is conservative relative to the potential for IDS reactors.…”
Section: Laboratory Bioreactor Reaction Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that prior animal operations within SW2 applied high amounts of manure to soils. Additionally, stream water hydrology at the SW2 outlet was drastically altered in April 1993 when beavers (Castor canadensis) created a 3.3 ha pond that temporarily impounded water (Hunt et al, 1999). We hypothesized that P from animal manure and inorganic P fertilizer from past cropping activity was transported into the stream and later deposited into the pond.…”
Section: Dp Concentrationsmentioning
confidence: 99%